2007
DOI: 10.1371/journal.pone.0000211
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Toxicity of Potassium Tellurite: Unveiling an Ancient Enigma

Abstract: Biochemical, genetic, enzymatic and molecular approaches were used to demonstrate, for the first time, that tellurite (TeO3 2−) toxicity in E. coli involves superoxide formation. This radical is derived, at least in part, from enzymatic TeO3 2− reduction. This conclusion is supported by the following observations made in K2TeO3-treated E. coli BW25113: i) induction of the ibpA gene encoding for the small heat shock protein IbpA, which has been associated with resistance to superoxide, ii) increase of cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
194
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(206 citation statements)
references
References 41 publications
11
194
0
1
Order By: Relevance
“…We found that YqhD was highly induced when cells were grown in the presence of K 2 TeO 3 . This result and the fact that an important pathway of tellurite toxicity involves superoxide generation (4,27) prompted us to evaluate the role that YqhD could have in E. coli resistance to tellurite and other oxidative stress elicitors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that YqhD was highly induced when cells were grown in the presence of K 2 TeO 3 . This result and the fact that an important pathway of tellurite toxicity involves superoxide generation (4,27) prompted us to evaluate the role that YqhD could have in E. coli resistance to tellurite and other oxidative stress elicitors.…”
Section: Discussionmentioning
confidence: 99%
“…Although cells overexpressing yqhD showed increased tolerance to compounds whose toxicity involves superoxide generation like paraquat and potassium tellurite (4,27), the hydroxyl radical-generating chromate anion (5), and hydrogen peroxide, E. coli ⌬yqhD showed increased sensitivity to all these compounds (Table 2). To assess whether YqhD-mediated resistance phenotype was also related to cytoplasm thiol depletion (especially GSH), the effect of YqhD on E. coli resistance to oxidant compounds that involve thiol oxidation like diamide and cadmium chloride (28) was determined.…”
Section: Yqhd Mediates Resistance To Ros Elicitors In E Coli-tomentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that tellurite toxicity results from the ability of tellurite to act as a strong oxidizing agent that damages a number of cell components (Taylor, 1999;Pérez et al, 2007). In the last years, however, available evidence shows that tellurite toxicity results from the generation of reactive oxygen species (ROS) (Borsetti et al, 2005;Calderón et al, 2006;Tremaroli et al, 2007;Pérez et al, 2007). ROS, such as hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2 -) and hydroxyl radical (OH˙), are typical byproducts of aerobic metabolism.…”
Section: The Enigma Of Tellurite Toxicitymentioning
confidence: 99%